2001
DOI: 10.1128/aem.67.1.198-205.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Studies on the Ecology of Listeria monocytogenes in the Smoked Fish Processing Industry

Abstract: We have applied molecular approaches, including PCR-based detection strategies and DNA fingerprinting methods, to study the ecology of Listeria monocytogenes in food processing environments. A total of 531 samples, including raw fish, fish during the cold-smoking process, finished product, and environmental samples, were collected from three smoked fish processing facilities during five visits to each facility. A total of 95 (17.9%) of the samples tested positive for L. monocytogenes using a commercial PCR sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
3
10

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(134 citation statements)
references
References 36 publications
(45 reference statements)
5
116
3
10
Order By: Relevance
“…Also, a Danish study indicated great plant-to-plant variation in contamination rate, thus from some plants all product samples were positive whereas other plants produced products where L. monocytogenes was not detected (Jorgensen and Huss, 1998). A similar conclusion was reached by Norton et al (2001) who visited five United States smoke houses over a 6-month period. Using ribotyping, the authors found that each smoke house harbored its own specific ribotype(s) of L. monocytogenes.…”
Section: Bacteriophages As Antibacterial Agents In Foodssupporting
confidence: 54%
See 2 more Smart Citations
“…Also, a Danish study indicated great plant-to-plant variation in contamination rate, thus from some plants all product samples were positive whereas other plants produced products where L. monocytogenes was not detected (Jorgensen and Huss, 1998). A similar conclusion was reached by Norton et al (2001) who visited five United States smoke houses over a 6-month period. Using ribotyping, the authors found that each smoke house harbored its own specific ribotype(s) of L. monocytogenes.…”
Section: Bacteriophages As Antibacterial Agents In Foodssupporting
confidence: 54%
“…In contrast, a number of other studies using molecular typing techniques have suggested that raw fish is not the major source of final product contamination; rather, contamination occurs primarily during processing (Fonnesbech Vogel et al, 2001a;Fonnesbech Vogel et al, 2001b;Norton et al, 2001). Fish processing is very diverse and includes a number of steps that vary with types of fish and types of intended product.…”
Section: Fish Processing Lines and Listeria Monocytogenes Contaminmentioning
confidence: 78%
See 1 more Smart Citation
“…Both manual and automated ribotyping methods have been widely used for subtyping of bacterial isolates (1,2,13,14,16,19), detection and tracking of human and animal listeriosis cases and outbreaks (9,36,38), and tracking of L. monocytogenes contamination patterns in food processing plants (28). While the restriction enzymes EcoRI and PvuII have been used most commonly for ribotyping (13,14), other restriction enzymes have also been used (2,19).…”
mentioning
confidence: 99%
“…The prevalence of the pathogen in raw salmon from Chile, Norway and the west coast of the US has been reported to be 8.0%, 21% and 29.5%, respectively (Hoffman et al 2003). In other studies the prevalence of L. monocytogenes has been found to be 7.8% for salmon in the USA (Norton et al 2001) and 7.4% in Denmark (Fonnesbech et al 2001). L. monocytogenes was isolated in rainbow trout from retail markets in USA from 54% of the 74 samples examined (Draughon et al 1999).…”
Section: Panda and Gargmentioning
confidence: 95%